Supply Liquid Organic Fertilizer NASA and Rice Husk Ash To The Chemical Properties Of The Soil On The Tomato Plant - Fitra Syawal Harahap; Rahmaniah; Roswita, Oesman; Iman, Arman (International Journal of Science, Technology & Management, 2020)
Efforts to improve tomato production can be done with the use of organic fertilizers derived from agricultural waste, manure, green manure, manure-human waste, and compost as a substitute source of nutrients. This study aims To determine the best combination between provision of organic fertilizer POC and Rice Husk Ash On the Chemical Properties of the Soil On the Tomato Plant. This research used randomized block design factorial consisting of 2 treatment factors, namely : the Concentration of POC NASA (N) consists of 4 levels, namely: N0 = 0% ( control), N1 = 1 cc/ liter of water, N2 = 2 cc/ liter of water, N3 = 3 cc/ liters of water. Organic fertilizer Rice Husk Ash (A) which consists of 3 levels, namely :A0 = 0 tons/ ha, A1 = 15 tons/ha (158 g/polybag), A2 = 30 ton/ha (316 g/polybag). The test map used is the Duncan Multiple Range Test (DMRT). As for the observed parameters, namely soil chemical properties include soil pH Methods Elektrometri, C-organic (%) Method of Walkley and Black, P-Available (%) Method of Bray II. The results showed that the Provision of Liquid Organic Fertilizer NASA and as much as 2 cc/ liter of water is able to increase the soil pH and C-organic. Provision of 30 ton/ha or equivalent to 316 g/polybag Rice Husk Ash is able to increase P-available and C-organic.